The Beauty of Communion: Form and Expression in Hans Urs Von Balthasar - Muttathottil, Rintle Mathew (Journal of Dharma, 2008)
Gregory Arby, The Beauty of Communion: Form and Expression in Hans Urs Von Balthasar, Bangalore: Asian Trading Corporation, 2007, pages: 323.